Students' Achievement Between Online and Offline English Learning - Nurfitri Nurfitri; Mochtar Marhum; Darmawan Darmawan; Mawardin M. Said; Ferry Rita; Aminah Suriaman; Rofiqoh Rofiqoh (Jurnal Pendidikan, Sains Sosial, dan Agama, 2022)
The difference between online and offline learning impacts the students' achievements in English learning. This study aimed to analyze the comparison between students' achievement in offline and online English learning. This study used mixed methods research between quantitative and qualitative research methods. The population of this research was 113 students. The researcher used the purposive sampling technique and took 28 respondents as the study's sample. The instrument of this study was students' achievement data, interviews, and observation. The result shows that the student who learned in offline learning had a higher score than those who learned in online learning. It was proved by the average score that students obtained. Students who knew offline got a score of 78.93. Meanwhile, students who learned online got a score of 75.00, indicating that offline learning is more effective than online learning. The data showed Sig. (2-tailed) value was 0.000 less than 0.05. That value significantly differed between students' online and offline learning achievement. These happen because of several problems that affect student achievement; students' less cohesiveness, being uncomfortable studying, lacking attention and motivation, and the limitations of supporting facilities in learning. It makes students lazy to learn English.